Formulasi Konsep Moderasi Islam M Mucharom Syifa - Syifa, M Mucharom (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2019)
Abstract: The religious phenomenon of Islam in post-reform Indonesia is thought to have experienced extremism and radicalism. The explosion of terrorism in the name of Islam that occurred between 1998 and 2018 made the face of Indonesian Islam in the world. Whereas in fact Islam in Indonesia is Islam that promotes moderate principles (tawassuth / washatiah) in preaching, namely taking a middle ground between the opposite two extreme poles. Da'wah method of Washatiyatul Islam or Moderation of Islam is a method of da'wah that emphasizes the Islamic values ​​of Rahmatan Lil Alamin. Da'wah is friendly with tradition, so it can grow in a multicultural and multi-religious society. It is this characteristic of accommodative Islam that is the stronghold of the prevention of radical religious ideas. This article using the epistemological-historical-holisitic approach wants to explore the concept of moderation of Islam in the context of the Indonesian nation and the shallowness of religious reasoning. As a result, none of the strong references say that the spread of Islam in ancient Archipelago was by radical means. The history of Islam in the archipelago has struggled with diverse localities. Islam is not present to break down or chop away existing traditions and local culture, but try to dialect with the context in which Islam is located. Because of its flexible nature, Islam is able to survive and develop so that it raises a new Islamic style that is unique and does not exist in any part of the world. Keywords: Moderation of Islam, Integration-Interconnection, Nationality Jurisprudence, Radicalism, Islam rahmatan lil alamin. Abstrak : Fenomena keagamaan islam di Indonesia pasca reformasi ditengarai banyak mengalami ekstrimisme dan radikalisme. Ledakan terorisme atas nama Islam yang terjadi antara tahun 1998 hingga 2018 menjadikan wajah Islam Indonesia mendapat sorotan di dunia. Padahal sejatinya Islam yang ada di Indonesia adalah Islam yang mengedepankan prinsip moderat (tawassuth/washatiah) dalam berdakwah, yaitu mengambil jalan tengah di antara dua kutub ekstrim yang berlawanan. Metode dakwah Washatiyatul Islam atau Moderasi Islam adalah metode dakwah yang mengedepankan nilai-nilai Islam Rahmatan Lil Alamin. Dakwah yang ramah dengan tradisi, sehingga dapat tumbuh dalam masyarakat yang multikultultural dan multireligi. Karakteristik Islam akomodatif inilah yang menjadi benteng pencegahan faham keagaamaan radikal. Artikel ini dengan menggunakan pendekatan epistemologis-historis-holisitik ingin menelisik konsep moderasi Islam dalam konteks bangsa Indonesia dan kedangkalan nalar beragama. Hasilnya, tak ada satupun referensi kuat yang mengatakan bahwa penyebaran Islam di Nusantara zaman dahulu adalah dengan cara-cara radikal. Sejarah Islam di Nusantara telah mengalami pergumulan dengan lokalitas yang beragam. Islam hadir bukan untuk mendobrak atau membabat habis tradisi dan budaya lokal yang ada, melainkan mencoba untuk berdialektika dengan konteks di mana Islam berada. Oleh karena sifat fleksibelnya itu, Islam mampu bertahan dan berkembang sehingga memunculkan corak keislaman baru yang khas dan tidak ada di belahan dunia manapun. Kata Kunci : Moderasi Islam, Integrasi-Interkoneksi, Fiqih Kebangsaan, Radikalisme, Islam rahmatan lil alamin.